Analisis Disiplin Kerja pada Pekerja Generasi Z - Layalia Maharani (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to understand the meaning of work discipline for Generation Z in the workplace, the challenges they face, and the role of management in supporting their work discipline. Generation Z, born between 1997 and 2012, exhibits unique characteristics that influence their interpretation of work and discipline in the workplace.  A qualitative research method with a case study approach was employed, involving in-depth interviews with five Generation Z employees in Indonesia. Data collection techniques included interviews, observations, and documentation. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings of the study revealed that (1) work discipline is understood as individual responsibility toward oneself and the job, with indicators such as punctuality, adherence to regulations, and accountability. (2) Challenges faced by Generation Z in maintaining work discipline include physical fatigue and mental stress caused by work pressure. (3) The role of management is crucial in creating a work environment that supports discipline, through effective leadership, adequate facilities, and continuous support. This research is expected to provide insights for companies to develop more effective strategies to attract and retain Generation Z employees.